MILITARY INTELLIGENCE STRATEGIES IN RESPONDING TO SECURITY THREATS IN PAPUA: STRATEGI INTELIJEN MILITER DALAM MERESPON ANCAMAN KEAMANAN DI PAPUA - Wing Sandya Udayanto; Arifuddin Uksan; Syaid Haryana (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
Papua faces a serious threat of terrorism, particularly from armed groups such as KKB, which are involved in various acts of violence. The background of this study aims to analyze military intelligence strategies in responding to security threats and their impact on community welfare. The research method employed is qualitative with a descriptive approach, utilizing interviews, observations, and document analysis. The findings indicate that military intelligence strategies focus on mapping and early detection of potential threats, as well as leveraging technology for information gathering. The discussion highlights the importance of collaboration between the military, local government, and relevant agencies in effectively responding to threats, as well as the role of TNI AD programs in enhancing community welfare. The conclusion of this study recommends the establishment of DESK PAPUA within the National Intelligence Agency (BIN) to address local issues, and emphasizes the need for a Smart Power approach to mitigate separatist impacts. Additional suggestions include the formation of a special agency to handle conflicts in Papua and the expansion of the Manunggal Air Program to remote areas to support sustainable development.